Greenland’s demography, 1700-2000: The interplay of economic activities and religion - Marquardt, Ole (Études/Inuit/Studies, 2002)
AbstractIn pre-colonial times and during the first two centuries of its colonial history, Greenland had the seal hunt as its all dominant economic base. This hunt was practised in two different ways. In South Greenland where waters are open all year round, the seal hunt from kayak reigned supreme. In North Greenland where waters are covered with ice for a long period of the year, the kayak hunt was therefore supplemented by various forms of seal hunting from the ice. Kayak hunting was a trade which involved high mortality rates. Drowning and — even more important as a cause of deaths — various diseases resulting from the hunter’s daily exposure to cold weather and water, and to rain or snow storms, caused the male hunters to die in earlier ages than the women. Hence, the sex ratio in the adult ages displayed a large female majority in South Greenland — and a slight female majority in the North.In pagan times, polygamy and various forms of promiscuity helped society to avoid a situation in which only a number of women equal to that of men could become mothers who bore their children as lawful wives of a hunter. With the conversion to Christianity these social institutions were quickly abolished. Instead of that, the Christian form of marriage — and the Christian ban on extra-marital sexual relations — was introduced. In some parts of South Greenland, the sex ratio was so imbalanced that it jeopardized the demographic reproduction of the local communities. In the 20th century the importance of seal hunting decreased as more and more Greenlanders were able to find their livelihood as fishermen, civil servants, construction workers etc. Parallel to this, the sex ratio became balanced and today’s Greenlandic population even has a slight male majority. Hence, whereas the exclusive right of existence of the Christian form of marriage was unsuited for the seal hunting South Greenland of the preceding centuries, the modern Greenland of the 20th century has a sex distribution which is suited to this particular form of marriage.